Role of the Anterior Center-Edge Angle on Acetabular Stress Distribution in Borderline Development Dysplastic of Hip Determined by Finite Element Analysis - Chen, Songhao; Zhang, Liqiang; Mei, Yuqian; Zhang, Hong; Hu, Yongcheng; Chen, Duanduan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The joint in hip dysplasia is more prone to develop osteoarthritis caused by higher contact pressure, especially on the socket. The lateral center-edge angle (LCEA) is the main index in determining hip dysplasia radiographically. However, it is still controversial about the pathological condition when the LCEA angle is in the range of 18°-25°. This uncertainty undoubtedly brings challenges for accurate diagnosis and subsequent treatments. Objective: The purpose of this study is to investigate the impact of anterior center-edge angle (ACEA) in mechanical stress distribution by establishing hip joint finite element models and providing insights into the comprehensive dysplasia severity. Methods: 116 patients diagnosed with borderline development dysplastic hip (BDDH) in the Fourth Medical Center of PLA General Hospital were enrolled. Nine patients were categorized into three LCEA groups with maximal ACEA differences. Patient-specific hip joint models were reconstructed from computed tomography scans, and cartilages, including the labrum, were built using an improved numerical method. The finite element analysis was carried out to compare the stress distribution characteristics caused by different ACEA. Results: The maximum stress of the acetabulum increases, and the high-stress region proceeds to the edge direction with the ACEA decline. Quantitative analysis showed that the area ratio of high pressure grows in the more minor ACEA cases, and the contact facies lunata area significantly impacts the stress distribution. Conclusions: For patients with BDDH, ACEA and the area of facies lunata both play essential roles in determining the severity of hip dysplasia and the mechanical mechanism preceding osteoarthritis.